Modeling the dry sliding wear behavior of Cu-4wt%Ni-TiC composites using response surface methodology. (2018) - Jha, Pushkar; Kumar Gautam, Rakesh; Tyagi, Rajnesh
Abstract: The present paper intends to optimize certain process parameters on the wear and friction properties of Cu-4 wt% Ni- x wt% TiC ( x = 0, 2 and 4 wt%) metal matrix composites by using response surface methodology (RSM). The dry sliding wear test was conducted using a pin-on-disc with different process parameters of applied load, weight percentage of TiC particles and sliding distance as process variables. Analysis of variance was applied to check the adequacy of the developed model. Mathematical models were developed to investigate the influence of process parameters on the responses at 95% confidence level. Developed surface and contour plots depicted the effect of main parameters and its interactions on the responses.